2015
DOI: 10.1007/s11307-014-0814-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lipid Oxidation Increases Glucose Metabolism and Enhances 2-Deoxy-2-[18F]Fluoro-d-Glucose Uptake in Prostate Cancer Mouse Xenografts

Abstract: PurposeProstate cancer (PCa) is the second most common cause of cancer-related death among men in the United States. Due to the lipid-driven metabolic phenotype of PCa, imaging with 2-deoxy-2-[18F]fluoro-d-glucose ([18F]FDG) is suboptimal, since tumors tend to have low avidity for glucose.ProceduresWe have used the fat oxidation inhibitor etomoxir (2-[6-(4-chlorophenoxy)-hexyl]oxirane-2-carboxylate) that targets carnitine-palmitoyl-transferase-1 (CPT-1) to increase glucose uptake in PCa cell lines. Small hairp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 42 publications
6
47
0
2
Order By: Relevance
“…[ 18 F]FDG-PET imaging was performed as described previously (Schlaepfer et al, 2015). We performed single-position, whole-body imaging by using a Siemens Inveon microPET scanner at the University of Colorado Cancer Center Animal Imaging Shared Resources (AISR).…”
Section: Star Methodsmentioning
confidence: 99%
“…[ 18 F]FDG-PET imaging was performed as described previously (Schlaepfer et al, 2015). We performed single-position, whole-body imaging by using a Siemens Inveon microPET scanner at the University of Colorado Cancer Center Animal Imaging Shared Resources (AISR).…”
Section: Star Methodsmentioning
confidence: 99%
“…Prior studies have demonstrated that while fatty acid oxidation (FAO) is conducted minimally in many cancer cells [59], it is important in prostate cancer cells [6062]. We thus hypothesized that fatty acids rescue viability and suppress AMPK activation in the Combo-treated cells through ATP production via β-oxidation.…”
Section: Resultsmentioning
confidence: 98%
“…It has been increasingly recognized that alterations in lipid metabolism are a hallmark of cancer [22, 31] and some evidence indicates that prostate cancer is associated with an increased reliance of fatty acid as a metabolic fuel and as a precursor for phospholipid production to generate cell membranes [36, 37]. Accordingly, we aimed to define the lipid profile of human prostate cancer tissues and hypothesized that obesity would alter the lipidome, potentially identifying a signature that might be prognostic for aggressive disease.…”
Section: Discussionmentioning
confidence: 99%